Calcium Influx Inhibition is Involved in the Hypotensive and Vasorelaxant Effects Induced by Yangambin - Islania Giselia Albuquerque Araújo; Darizy Flávia Silva; Maria do Carmo de Alustau; Katy Lísias Gondim Dias; Karla Veruska Marques Cavalcante; Robson Cavalcante Veras; José Maria Barbosa-Filho; Mario dos Anjos Neto; Lusiane Maria Bendhack; Nadja de Azevedo Correia; Isac Almeida de Medeiros (Molecules, 2014)
The pharmacological effects on the cardiovascular system of yangambin, a lignan isolated from Ocotea duckei Vattimo (Lauraceae), were studied in rats using combined functional and biochemical approaches. In non-anaesthetized rats, yangambin (1, 5, 10, 20, 30 mg/kg, i.v.) induced hypotension (−3.5 ± 0.2; −7.1 ± 0.8; −8.9 ± 1.3; −14 ± 2.3, −25.5% ± 2.6%, respectively) accompanied by tachycardia (5.9 ± 0.5; 5.9 ± 1.6; 8.8 ± 1.4; 11.6, 18.8% ± 3.4%, respectively). In isolated rat atria, yangambin (0.1 µM–1 mM) had very slight negative inotropic (Emax = 35.6% ± 6.4%) and chronotropic effects (Emax = 10.2% ± 2.9%). In endothelium-intact rat mesenteric artery, yangambin (0.1 µM–1 mM) induced concentration-dependent relaxation (pD2 = 4.5 ± 0.06) of contractions induced by phenylephrine and this effect was not affected by removal of the endothelium. Interestingly, like nifedipine, the relaxant effect induced by yangambin was more potent on the contractile response induced by KCl 80 mM (pD2 = 4.8 ± 0.05) when compared to that induced by phenylephrine. Furthermore, yangambin inhibited CaCl2-induced contractions in a concentration-dependent manner. This lignan also induced relaxation (pD2 = 4.0 ± 0.04) of isolated arteries pre-contracted with S(−)-Bay K 8644. In fura-2/AM-loaded myocytes of rat mesenteric arteries, yangambin inhibited the Ca2+ signal evoked by KCl 60 mM. In conclusion, these results suggest that the hypotensive effect of yangambin is probably due to a peripheral vasodilatation that involves, at least, the inhibition the Ca2+ influx through voltage-gated Ca2+ channels.